Achievement-motivated behavior in Individual sports (AMBIS-I)—coach rating scale - Zuber, C.; Conzelmann, A. (German Journal of Exercise and Sport Research, 2019)
The assessment of achievement motivation in the context of selection decisions in elite youth sports is associated with serious problems (e.g. socially desirable responses). In order to counteract such problems, an external rating scale for the assessment of the Achievement-Motivated Behavior in Individual Sports (AMBIS-I) from a coach`s perspective was constructed and checked for psychometric quality in three consecutive steps. The studies are based on four different German-speaking samples, including 101 experienced coaches from individual sports and 26 sport psychologists. Multiple phases of exploratory structural equation modeling, item removal and cross-validation unveiled a three-factorial model with 10 items displaying excellent fit indices, acceptable to good reliability, and evidence based on internal structure. Relationships with athletes` performance level point to the instrument`s evidence for test-criterion relationship. These preliminary results are promising when considering the construction and show the potential of the economical coach rating scale for the scientifically sound assessment of observable achievement-motivated behavior in individual sports.